44. Stance postural strategies in patients with chronic inflammatory demyelinating polyradiculoneuropathy. Issue 12 (December 2016) - Rinalduzzi, S.; Capozza, M.; Accornero, N.; Missori, P.; Trompetto, C.; Fattapposta, F.; Currá, A.
Abstract : Human postural control can be studied with the single- or multi-link inverted pendulum model. This model assumes two postural strategies (hip and ankle). Polyneuropathy leads to postural instability and an increased risk of falling. We investigated how impaired motor impairment and proprioceptive input due to neuropathy influences postural strategies. Platformless bisegmental posturography data were recorded in healthy subjects and patients with chronic inflammatory demyelinating polyradiculoneuropathy (CIDP). Each subject stood on the floor, wore a head and a hip electromagnetic tracker. Sway amplitude, velocity were recorded and kinemtaic analisys (reflecting postural strategies by mean direction difference or MDD in the velocity vector between trackers) was calculated. Head and hip postural sway increased more in patients with CIDP than in healthy controls. MDD values reflecting hip strategies also increased more in patients than in controls. In the eyes closed condition MDD values in healthy subjects decreased but in patients remained unchanged. Sensori-motor impairment changes the balance of postural strategies that patients adopt to maintain upright quiet stance. Motor impairment leads to hip postural strategy overweight (eyes open), and prevents strategy re-balancing when the sensory context predominantly relies on proprioceptive input (eyes closed).